NOVEL PROSES INDIVIDUASI DIRI DALAM FIGHT CLUB KARYA CHUCK PALAHNIUK - ISMAYA, CHRISTIA ADAM; SIGARLAKI, STEPHANI J.; LASUT, THERESIA M.C. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThis research is entitled â€œProses Individuasi Diri dalam Novel Fight Club Karya Chuck Palahniukâ€. The objectives of this research are to identify and analyze the depiction of the self individuation process on the novel Fight Club by Chuck Palahniuk based on Carl Gustav Jungâ€™s theories.The writer uses prsychological approach, qualitative research and narrative analysis in order to identify how the self individuation process depicted in the novel especially in the main character. The writer uses the theory of characterization by Roberts and Jacobs (1989) as the tools of this research.The result of this research shows that the main character of the novel undergoes the process of individuation and we can see how the characeristics, steps, and the achievement of individuation being depicted through the story and the characterization of the main character.Â Â Keywords: Individuation Process, The true self, Archetypes, Fight Club